Effect of the chronic administration of caffeine on adipose mass and lipid profile of Wistar rats - doi: 10.4025/actascibiolsci.v35i2.11085 - Nakagawa, Priscila; Pedrosa, Maria Montserrat Diaz (Acta Scientiarum. Biological Sciences, 2012)
This work aimed at verifying the effect of the chronic ingestion of caffeine on body weight and adiposity of Wistar rats. Sixteen male Wistar rats weighting on average 240 g were divided into two groups, one control and the other caffeine-treated (5 mg kg-1, orally) for five weeks. At the end, the groups were evaluated for their differences in body weight; weight of the periepididymal, retroperitoneal, subcutaneous and mesenteric fat pads; size of the retroperitoneal adipocytes; liver and heart weight; glycemia and plasma lipids. Statistically significant differences were observed in adipocyte size and total serum cholesterol, while the results for the other parameters were not statistically different. Therefore, this study showed that, using an oral dose of caffeine within acceptable (non toxic) limits, it is possible to reduce the size of adipocytes of non-obese Wistar rats, as well as to reduce the serum cholesterol levels, even in the absence of physical activity or other active compounds.